Predictors of successful trial of labor after cesarean section (TOLAC) in women with one prior transverse cesarean section at Tertiary Hospitals in northwest Ethiopia: a multicenter study - Gizachew Aynalem Tegegne; Bayew Kelkay Rade; Ayenew Engida Yismaw; Worku Taye; Berihun Agegn Mengistie (BMC, 2024)
Abstract Background Trials of labor after cesarean section is the preferred strategy to decrease the cesarean delivery rate and reducing complications associated with multiple cesarean sections. The success rate of trials of labor after cesarean section and associated factors have not been well documented in Ethiopia. Hence, this study was aimed to determine the success rate and factors associated with the trial of labor after one cesarean section in five Comprehensive Specialized Hospitals located in northwest Ethiopia. Methods An institutional-based cross-sectional study was conducted among 437 women who came for the trial of labor from December 1, 2021, to March 30, 2022. All women who fulfilled the eligibility criteria were included to this study. Data was collected using structured and pre-tested questionnaire. Then, the data was entered into Epi Data 4.6 software and exported to SPSS version 26 for analysis. To identify the variables influencing the outcome variable, bivariable and multivariable logistic regression analyses were conducted. The model's fitness was checked using the Hosmer-Lemeshow goodness of fit test, and an adjusted odds ratio with a 95% confidence interval was used to declare the predictors that are significantly associated with TOLAC. Results The success rate of the trial of labor after one cesarean section was 56.3% (95% CI, 51.3%, 61.2%). Maternal age ≥ 35 years (AOR: 3.3, 95% CI 1.2, 9.3), the fetal station at admission ≤ zero (AOR: 5. 6, 95% CI 3.3, 9.5), vaginal delivery before cesarean section (AOR: 1.9, 95% CI 1.2, 3.2), and successful vaginal birth after cesarean delivery (AOR 2.2, 95% CI 1.2, 4.1) were found to have a significant association with the success rate of trial of labor after cesarean section. Conclusions In this study, the success rate of the trial of labor after a cesarean section was low as compared to the ACOG guideline and other studies in different countries. Therefore, the clinicians ought to offer counsel during antenatal and intrapartum period, encourage the women to make informed decision on the mode of delivery, and the practitioners need to follow fetal and maternal conditions strictly to minimize adverse birth outcomes.